A DIGEST OF ACTS OF ASSEMBLY, RELATING TO THE INCORPORATED DISTRICT OF THE NORTHERN LIBERTIES, at 94, Ordinance of Nov. 6, 1815, § 7 (1847) - (:unkn) unknown (My University, 1815)
Prohibited discharge of any cannon, artillery, small arms, or prove any pistol, gun, musket barrels, cannon, or illuminate any house. Violators forfeit the weapons and fined two dollars.
Keywords: DISCHARGE